Analisis Resiko Usaha Tani (Potensi Bencana) Terhadap Produktivitas Padi Sawah di Kabupaten Padang Pariaman - Khairani Khairani; Mike Triani; Novya Zulfa Riani (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of farming risk on lowland rice productivity in Padang Pariaman. Variables used to assist farming risk are water availability, floods, landslides, river abrasion and rice pests. This research is descriptive and associative. The data used is secondary data from 2018 to 2020 obtained from related institutions. With the panel data regression model, the selected model is the Fixed Effect Model. The results of this study indicate that simultaneously the availability of water, the potential for flooding, the potential for landslides, the potential for river abrasion, and the level of pest attack on rice have a significant effect on rice productivity in Padang Pariaman. Furthermore, partially (1) water has a significant effect on 10% alpha and has a positive effect on lowland rice productivity in Padang Pariaman; (2) The potential for flood disaster has a significant effect on the 10% error and has a negative effect on the productivity of lowland rice in Padang Pariaman; (3) The potential for landslides has a significant and negative effect on the productivity of lowland rice in Padang Pariaman; (4) The potential for river abrasion does not have a significant and positive effect on the productivity of lowland rice in Padang Pariaman; (5) The level of pest attack has no significant and positive effect on the productivity of lowland rice in Padang Pariaman.